Cataract Blindness and Simulation-Based Training for Cataract Surgeons An Assessment of the HelpMeSee Approach - Broyles, James R. (RAND Corporation, 2012)
Cataracts cause about half of all cases of blindness worldwide, largely in developing countries. HelpMeSee Inc. is developing a simulator-based method for rapid cataract surgical training that RAND researchers determined could significantly help to close the backlog of cataract cases, expected to be 32 million globally by 2020. For this to occur, challenges in the areas of outreach, quality monitoring, and public acceptance must be met.